The Contribution of State-Owned Enterprises to Climate Change Mitigation in China - Mayer Benoit; Rajavuori Mikko; Fang Mandy Meng (IOS Press, 2022)
China plans the implementation of a nationwide market-based mechanism for greenhouse gas mitigation, appearing thus to replicate the method used most notably in the European Union to price greenhouse gas emissions. However, China’s new mechanism represents only be the tip of the mitigation iceberg. Banking on the unique characteristics of a socialist market economy, China’s government has largely relied on State-Owned Enterprises as a tool for implementing rapid change. In this article, we discuss the role played by Chinese SOEs to advance the country’s ambitious mitigation objectives. After a general description of the incentives created for emission limitation and energy saving through SOE supervision, we highlight the corresponding efforts made in the fossil-fuel, power-generation, and other key mitigation sectors.